TINJAUAN YURIDIS TERHADAP PENERAPAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA (STUDI PUTUSAN NO 46/PID.SUS/ 2019 PENGADILAN NEGERI MAUMERE) - Ndaumanu, Novaldy I; Sinurat, Aksi; Wilhelmus, Bhisa Vitus (Petitum Law Journal, 2024)
The quality of the judge's decision in adjudicating is when the judge is able to hand down a decision by paying attention to three very essential things, namely legal certainty, justice, and expediency. Interpreting the element of